2015
DOI: 10.19129/sbad.19
|View full text |Cite
|
Sign up to set email alerts
|

Kırsal Kadınların Girişimcilik Özellikleri ve Girişimciliği Etkileyen Faktörlerin Logit Analizi İle Değerlendirilmesi (Hatay İli Araştırması)

Abstract: Bu araştırmada; Hatay İli kırsalındaki kadınların girişimcilik özellikleri ve girişimcilik rollerini etkileyen faktörler araştırılmıştır. Araştırma Hatay İli Merkez ve İlçelerine bağlı toplam 21 köyde ve belediyelerde yaşayan 120 kırsal kadını kapsamaktadır. Araştırmada kullanılan veriler anket tekniği ile elde edilmiştir. Analiz aşamasında ise Lojistik Regresyon kullanılmıştır. Araştırmaya katılan kadınların girişimciliğini etkileyen faktörleri bulmak amacıyla yapılan Lojistik Regresyon analizinde kadınların … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
6
0
1
Order By: Relevance
“…Although the relationship was found to be significant between the land size and awareness level, x 2 critical (21.026) and x 2 calculated (21.024) values were very close to each other (Table 6). Indeed, Kızılaslan and Kızılaslan (2005) could not find a relationship between the level of awareness and land size. Table 4.…”
Section: Likert Scale and Assessment Of Pesticide Use Consciousnessmentioning
confidence: 83%
See 3 more Smart Citations
“…Although the relationship was found to be significant between the land size and awareness level, x 2 critical (21.026) and x 2 calculated (21.024) values were very close to each other (Table 6). Indeed, Kızılaslan and Kızılaslan (2005) could not find a relationship between the level of awareness and land size. Table 4.…”
Section: Likert Scale and Assessment Of Pesticide Use Consciousnessmentioning
confidence: 83%
“…In another study, relationship between the knowledge level and education was found to be significant and coefficient contingency was 0.344 (Erdil and Tiryaki 2020). Kızılaslan and Kızılaslan (2005) reported significant correlations of farmers' awareness with age and education.…”
Section: Likert Scale and Assessment Of Pesticide Use Consciousnessmentioning
confidence: 91%
See 2 more Smart Citations
“…Şırnak'ta yapılan bir başka çalışmada ise erkek girişimcilerin kadın girişimcilere göre belirsizliğe karşı toleransı yüksek olduğu bulgulanmıştır (Ece, 2019). Kadın girişimcilerin yaşadıkları sorun ve engeller üzerine yapılan araştırmalarda, sermaye ve finans bulma güçlüğü (Özkaya, 2009;Şahin, 2009;Karabat ve Sönmez, 2012;Çabuk, Doğan Südaş ve Köksal Araç, 2015;Kızılaslan ve Karaömer, 2015;Ballı, 2017;Mukovic, 2018;Filizöz ve Yaraş, 2020;Erol ve Çiçek 2020;Solmaz ve Özdemir, 2021) yaşadıkları vurgulanmıştır. Kadın girişimcilerin kurdukları işletme profili sonuçlarında ise ağırlıklı girişimlerin hizmet sektöründe faaliyet gösterdikleri ve mikro ölçekli yapılanmalar şeklinde kurulduğu yer almaktadır (Yirik ve Yıldırım, 2014;Bozat, 2017;Çağıran Kendirli ve Şenöz, 2019;Uygun ve Günaydın, 2019;Acar ve Çağlar, 2019;Selvi Hanişoğlu ve Özgür, 2021;Morkoç, Karabulut, Aktaşoğlu ve Arslan, 2021;Taşdemir, 2021;Büyükbeşe vd., 2022;Şencan Kukuş ve Sırkıntıoğlu Yıldırım, 2023).…”
Section: Literatür Taramasıunclassified